Sodium hydroxide modified biochar composite material as well as preparation method and application thereof
Through the application of sodium hydroxide modified biochar composite materials, the problem of heavy metal treatment in the solid phase is solved, and the heavy metal removal effect is achieved with high efficiency, low cost and environmentally friendly, and is suitable for heavy metal adsorption and passivation in the composting system.
Patent Information
- Application Number
- CN202411610746.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-02-21
AI Technical Summary
The prior art is difficult to effectively remove heavy metals in the solid phase, and traditional treatment methods have problems with high cost, complex operations and secondary pollution risks.
Using sodium hydroxide modified biochar composite material, biochar is prepared by pyrolysis of agricultural waste materials and mixed with sodium hydroxide solution. The obtained material after modification is used for adsorption and passivation of heavy metals in the composting system.
It has achieved low-cost and efficient removal of harmful heavy metal ions such as lead, cadmium, chromium and other harmful metal ions in water, protects water resources security, and avoids secondary pollution, which is in line with the concept of green development.
Smart Images

Figure CN119488891A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of heavy metal treatment in a solid phase, and in particular relates to a sodium hydroxide modified biochar composite material and a preparation method and application thereof. Background Art
[0002] Heavy metal pollution refers to environmental pollution caused by heavy metals or their compounds, which is mainly caused by human factors such as mining, exhaust gas emissions, sewage irrigation and the use of products with excessive heavy metals. They are likely to cause serious water and soil pollution, damage the ecological environment, and thus cause harm to human health. Heavy metals mainly exist in the solid phase (soil or manure, etc.) or the liquid phase (various types of wastewater). Most adsorption materials or adsorption methods target heavy metals in solution. Compared with the liquid phase, the mobility of heavy metals in the solid phase is not strong and it is impossible to extract and recover them. This is the main reason for the difficulty in their treatment. How to remove heavy metals in the solid phase is still a difficult problem in environmental governance.
[0003] At present, the engineering methods for treating these pollutants are roughly divided into physical remediation technology, chemical remediation technology and biological remediation technology. Among physical remediation technologies, chemical polymers have better suitability and effectiveness for low-concentration pollutants. Their relatively high cost is a practical obstacle to their promotion and application, and their natural mineral composition is complex, and the release of associated minerals and impurities poses a high risk of secondary pollution. Although chemical remediation technology can change the form of heavy metals by adding chemical reagents or using chemical reactions to make them easier to remove or fix, the use of chemical reagents may introduce new pollutants and increase the burden on the environment. Secondly, chemical remediation technology often requires complex operating procedures and fine parameter control, and may cause secondary pollution if not carefully; long-term and large-scale use of chemical reagents may also damage soil microbial communities and affect the ecological balance of the soil. The treatment efficiency of biological remediation technology is often low, and it takes a long time to achieve the ideal treatment effect. Secondly, the applicability of biological remediation technology is limited. It is mainly suitable for situations with light pollution and good soil environment. In areas with severe heavy metal pollution, the effect of biological remediation technology is not ideal. In addition, the biological remediation process may also be interfered by environmental factors (such as temperature, humidity, pH value, etc.), affecting the treatment effect.
[0004] Therefore, considering the adsorption effect, economic feasibility and environmental friendliness, it is necessary to develop new green adsorbents. Summary of the invention
[0005] In order to overcome the shortcomings of the above-mentioned prior art, the purpose of the present invention is to provide a sodium hydroxide modified biochar composite material and a preparation method and application thereof. The sodium hydroxide modified biochar composite material can be used for the adsorption and passivation of heavy metals in the composting system, and has the advantages of low cost, good effect, strong operability, no secondary pollution, beautification of the environment, etc.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions: In a first aspect, the present invention provides a method for preparing a sodium hydroxide modified biochar composite material, comprising the following steps: The agricultural waste material is shredded, cleaned, dried, and then sealed. After standing, an inert atmosphere is introduced for pyrolysis reaction. After cooling, grinding, and sieving, a crude biochar is obtained. The crude biochar is mixed with a sodium hydroxide solution, and the liquid is filtered out after shaking to leave the solid. The solid is washed until the filtrate is neutral, and then dried to obtain a sodium hydroxide-modified biochar composite material. The solid-liquid ratio of the crude biochar to the sodium hydroxide solution is 1 g: (5-10) mL. The concentration of the sodium hydroxide solution is 1.0-4.0 mol / L.
[0007] Preferably, the agricultural waste material includes one or more of dry straw, wood chips, dry grass, dry leaves and dry branches.
[0008] Preferably, the drying temperature is 60-80°C.
[0009] Preferably, the conditions of the pyrolysis reaction are: pyrolysis at 600-650° C. for 2-6 hours.
[0010] Preferably, the heating rate of the pyrolysis reaction is 5-10°C / min.
[0011] Preferably, the particle size of the crude biochar is less than 100 mesh.
[0012] Preferably, the shaking condition is: shaking at a speed of 120-180 r / min for 6-8 h at 15-40° C.
[0013] Preferably, the cleaning is carried out using deionized water.
[0014] In a second aspect, the present invention provides a sodium hydroxide modified biochar composite material.
[0015] In a third aspect, the present invention provides an application of a sodium hydroxide modified biochar composite material in the adsorption and passivation of heavy metals in compost.
[0016] Compared with the prior art, the present invention has the following beneficial effects: The raw materials of the present invention are agricultural waste materials, which are converted into valuable biochar materials, which not only realizes the resource utilization of agricultural wastes and reduces the dependence on traditional energy, but also avoids the environmental pollution problems that may be caused by waste accumulation, which is in line with the concept of circular economy and green development; through the modification treatment of sodium hydroxide solution, the surface structure and chemical properties of biochar are significantly improved, and the strong alkalinity of sodium hydroxide can increase the number of negative charges on the surface of biochar, improve its hydrophilicity, and introduce more functional groups, such as hydroxyl, carboxyl, etc., which have strong adsorption capacity for heavy metal ions. Therefore, the modified biochar composite material shows higher efficiency and wider application range in heavy metal pollution control, and can effectively remove harmful heavy metal ions such as lead, cadmium, chromium, etc. in water, and protect water resources safety. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 is an X-ray crystal diffraction (XRD) spectrum of the sodium hydroxide modified biochar of Example 1 of the present invention; Figure 2 is a specific surface area (BET) diagram of the sodium hydroxide modified biochar of Example 1 of the present invention; Figure 3 is a scanning electron microscope (SEM) image of the sodium hydroxide modified biochar of Example 1 of the present invention; Figure 4 This is an energy dispersive X-ray spectrometer (EDS) elemental composition distribution spectrum of the sodium hydroxide modified biochar of Example 1 of the present invention; Figure 5 The effect of sodium hydroxide modified biochar of Example 1 of the present invention on the morphological distribution of heavy metals (Cd, Pb, Cr, As) in compost (chicken manure and bagasse); Figure 6 is the passivation rate of heavy metals (Cd, Pb, Cr, As) in compost (chicken manure and bagasse) by the sodium hydroxide modified biochar of Example 1 of the present invention; Figure 7 is the passivation rate of heavy metals (Cd, Pb, Cr, As) in compost (sludge and straw) by the sodium hydroxide modified biochar of Example 1 of the present invention; Figure 8 It is the passivation rate of heavy metals (Cd, Pb, Cr, As) in compost (pig manure, chicken manure, cow manure and corn straw) by the sodium hydroxide modified biochar of Example 1 of the present invention. DETAILED DESCRIPTION
[0018] In order to enable those skilled in the art to better understand the scheme of the present invention, the technical scheme in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0019] It should be understood that when used in this specification and the appended claims, the terms "include" and "comprises" indicate the presence of described features, integers, steps, operations, elements and / or components, but do not exclude the presence or addition of one or more other features, integers, steps, operations, elements, components and / or combinations thereof.
[0020] It should also be understood that the terms used in the present specification are only for the purpose of describing specific embodiments and are not intended to limit the present invention. As used in the present specification and the appended claims, unless the context clearly indicates otherwise, the singular forms "a", "an" and "the" are intended to include plural forms.
[0021] It should be further understood that the term "and / or" used in the present description and the appended claims refers to any and all possible combinations of one or more of the associated listed items, and includes these combinations.
[0022] Various structural schematic diagrams of the embodiments disclosed in the present invention are shown in the accompanying drawings. These figures are not drawn to scale, and some details are magnified and some details may be omitted for the purpose of clear expression. The shapes of various regions and layers shown in the figures and the relative sizes and positional relationships therebetween are only exemplary, and may deviate in practice due to manufacturing tolerances or technical limitations, and those skilled in the art may additionally design regions / layers with different shapes, sizes, and relative positions according to actual needs.
[0023] The present invention is further described in detail below in conjunction with the accompanying drawings: Biomass is widely available, low-cost, environmentally friendly and renewable, and the pyrolysis of biomass in an oxygen-free environment helps convert most organic compounds into highly aromatic, carbon-rich, and highly stable insoluble solid porous biochar, which shows great potential in heavy metals and pollutants. However, the pore structure of unmodified biochar is not well developed, and the distribution of surface functional groups is not reasonable, so it has poor performance in the adsorption of heavy metals. Biochar itself has more unobstructed pores and better specific surface area, which has better application potential in heavy metal adsorption. Therefore, the first purpose of the present invention is to provide a method for preparing a sodium hydroxide modified biochar composite material, comprising the following steps: Cut the agricultural waste material into small pieces and wash them several times. After washing with deionized water, flatten them and put them into an oven to dry at 60-80°C. After drying, put them into a ceramic jar and seal them with a lid. After standing, introduce an inert atmosphere and heat them to 600-650°C at a rate of 5-10°C / min under an inert atmosphere. Pyrolyze them for 2-6 hours. After cooling and grinding, pass them through a nylon sieve to retain the crude biochar with a particle size less than 100 mesh. The crude biochar with a particle size less than 100 mesh is mixed with a sodium hydroxide solution at a solid-liquid ratio of 1g: (5-10) mL, wherein the concentration of the sodium hydroxide solution is 1.0-4.0 mol / L. After mixing, the mixture is placed in an oscillator and oscillated at 120-180 r / min for 6-8 hours at 15-40°C; the liquid is filtered to remove the solid, and the solid is washed with deionized water until the filtrate is neutral or nearly neutral; the washed solid is dried at 60-80°C to constant weight to obtain a sodium hydroxide-modified biochar composite material, which can be packed into a sealed bag for storage.
[0024] The present invention mixes sodium hydroxide solution with biochar to prepare a sodium hydroxide modified biochar composite material, which can solve the problems of underdeveloped pore structure and unreasonable distribution of surface functional groups of unmodified biochar, and solves the problem of unstable heavy metal adsorption performance of unmodified biochar in compost. While improving material performance, it can also increase the removal capacity of various heavy metal pollution in the composting system, and can also synergistically reduce the emission of gaseous pollutants in the composting process.
[0025] Specifically, the agricultural waste materials include one or more of dry straw, sawdust, dry grass, dry leaves and dry branches. The dry straw includes dry wheat straw and dry corn straw. Agricultural and forestry waste materials are produced in large quantities on a daily basis and have high organic matter content. Improper treatment can easily cause environmental pollution. The present invention uses such agricultural and forestry organic waste as raw materials, which can be obtained in large quantities without investing additional costs. The agricultural and forestry organic waste is pyrolyzed to prepare biochar materials, which can convert waste into resources with application value, and has good adsorption capacity for high-risk heavy metal pollutants, and has potential engineering application value.
[0026] The second purpose of the present invention is to provide a sodium hydroxide modified biochar composite material. The sodium hydroxide modified biochar composite material not only has rich functional groups and developed pores, but also exhibits excellent adsorption capacity, and can be used as an effective material for compost heavy metal adsorption.
[0027] The third purpose of the present invention is to provide an application of a sodium hydroxide modified biochar composite material in the adsorption and passivation of compost heavy metals. The sodium hydroxide modified biochar not only has excellent passivation ability for a single heavy metal, but can also adsorb and passivate multiple heavy metals at the same time. In addition, it can be used as an adsorbent and also as a soil modifier and directly returned to the field with the compost product.
[0028] Example 1 Cut the dry wheat straw into small pieces (0.1-0.5 mm), wash them three times, rinse them with deionized water, flatten them and put them in an oven to dry at 80°C. Take a certain amount of dry wheat straw pieces and put them in a ceramic jar, cover it with a lid, seal it with tin foil, let it stand, heat it to 600°C at a rate of 10°C / min in an inert atmosphere, pyrolyze it for 6h, cool it, grind it and pass it through a nylon sieve, and keep the crude biochar with a particle size less than 100 mesh; The crude biochar was mixed with 2.0 mol / L sodium hydroxide solution at a solid-liquid ratio of 1 g:8 mL, placed in an oscillator and oscillated at 180 r / min at 30 °C for 6 h, the liquid was filtered out to leave the solid, and the solid was repeatedly washed with deionized water until the filtrate was neutral. The solid was dried at 70 °C to constant weight to obtain a sodium hydroxide-modified biochar composite material, which was put into a sealed bag and stored for later use.
[0029] X-ray diffraction (XRD) was performed on the sodium hydroxide modified biochar composite material obtained in this example. Figure 1 As shown; and the specific surface area (BET) analysis was performed, such as Figure 2 shown; according to Figure 1 and Figure 2 It was found that the specific surface area and pore volume of the biochar composite modified by sodium hydroxide increased by 3.02 times and 28.39%, respectively.
[0030] The sodium hydroxide modified biochar composite material obtained in this example was scanned by a scanning electron microscope (SEM). Figure 3 As shown; and energy dispersive X-ray spectrometer (EDS) analysis, such as Figure 4 shown; according to Figure 3 and Figure 4 It was found that the sodium hydroxide-modified biochar composite material significantly increased the O element content by 16.89%.
[0031] Example 2 Cut the dry corn stalks into small pieces and wash them three times, rinse them with deionized water, flatten them and put them in an oven to dry at 60°C, take a certain amount of dry corn stalks and put them in a ceramic jar, cover them with a lid and seal them, let them stand, heat them to 650°C at a rate of 5°C / min in an inert atmosphere, pyrolyze them for 2h, cool them, grind them and pass them through a nylon sieve, and keep the crude biochar with a particle size less than 100 mesh; The crude biochar was mixed with a 1.0 mol / L solution at a solid-liquid ratio of 1 g:10 mL, placed in an oscillator and oscillated at 120 r / min at 40 °C for 8 h, the liquid was filtered out to leave the solid, and the solid was repeatedly washed with deionized water until the filtrate was close to neutral. The solid was dried at 80 °C to constant weight to obtain a sodium hydroxide-modified biochar composite material, which was put into a sealed bag and stored for later use.
[0032] The specific surface area (BET) analysis of the sodium hydroxide modified biochar composite material obtained in this example found that the specific surface area and pore volume of the sodium hydroxide modified biochar composite material increased by 2.76 times and 23.93%, respectively.
[0033] Example 3 Cut the dry branches into small pieces and wash them three times, rinse them with deionized water, flatten them and put them in an oven at 70°C for drying. Take a certain amount of dry branches and put them in a ceramic jar, cover it with a lid and seal it, then heat it to 600°C at a rate of 20°C / min in an inert atmosphere, pyrolyze it for 4h, cool it, grind it and pass it through a nylon sieve, and keep the crude biochar with a particle size less than 100 mesh; The crude biochar was mixed with a 4.0 mol / L solution at a solid-liquid ratio of 1 g:5 mL, placed in an oscillator at 15°C and oscillated at 180 r / min for 6 h. After being taken out, the solid and liquid were separated. The solid was then repeatedly washed with a large amount of deionized water until the filtrate was close to neutral. The solid was dried at 60°C to constant weight to obtain a sodium hydroxide-modified biochar composite material, which was then put into a sealed bag and stored for later use.
[0034] The specific surface area (BET) analysis of the sodium hydroxide modified biochar obtained in this example found that the specific surface area and pore volume of the sodium hydroxide modified biochar composite material increased by 4.34 times and 38.57%, respectively.
[0035] Example 4 Cut a mixture of dry branches, dry wheat straw, dry leaves, dry corn straw and dry grass into small pieces, wash them three times, rinse them with deionized water, flatten them and put them in an oven to dry at 80°C, take a certain amount of dry mixture pieces and put them in a ceramic jar, cover it with a lid and seal it, let it stand, heat it to 650°C at a rate of 10°C / min in an inert atmosphere, pyrolyze it for 3h, cool it, grind it and pass it through a nylon sieve, and keep the crude biochar with a particle size less than 100 mesh; The crude biochar was mixed with a 2.0 mol / L solution at a solid-liquid ratio of 1 g:5 mL, placed in an oscillator and oscillated at 150 r / min for 4 h at 25 °C, the liquid was filtered out to leave the solid, and the solid was repeatedly washed with deionized water until the filtrate was close to neutral. The solid was dried at 60 °C to constant weight to obtain a sodium hydroxide-modified biochar composite material, which was put into a sealed bag and stored for later use.
[0036] The specific surface area (BET) analysis of the sodium hydroxide-modified biochar composite material obtained in this example showed that the specific surface area and pore volume of the biochar after sodium hydroxide modification increased by 5.72 times and 41.61%, respectively.
[0037] Example 5 A mixture of dry wheat straw, sawdust, dry grass, dry leaves and dry branches was cut into small pieces and washed three times, washed with deionized water, flattened and placed in an oven to dry at 80°C, a certain amount of dry mixture was placed in a ceramic jar, covered with a lid and sealed, and after standing, the temperature was raised to 650°C at a rate of 8°C / min in an inert atmosphere, pyrolyzed for 3h, cooled, ground and passed through a nylon sieve, and the crude biochar with a particle size of less than 100 mesh was retained; The crude biochar was mixed with a 2.0 mol / L solution at a solid-liquid ratio of 1 g:5 mL, placed in an oscillator and oscillated at 150 r / min for 4 h at 25 °C, the liquid was filtered out to leave the solid, and the solid was repeatedly washed with deionized water until the filtrate was close to neutral. The solid was dried at 60 °C to constant weight to obtain a sodium hydroxide-modified biochar composite material, which was put into a sealed bag and stored for later use.
[0038] The sodium hydroxide modified biochar composite materials and the crude biochar (unmodified biochar) prepared in Examples 1 to 4 were used as adsorption materials, respectively, to evaluate their adsorption and passivation capabilities for heavy metal ions in solution.
[0039] Specifically: in a 100mL solution of different heavy metals (including Cd 2+ , Pb 2+ ,Cr 6+ , As 5+ The concentration of the solution was 100 mg / L. 1 g of sodium hydroxide modified biochar composite material or unmodified biochar was added to a triangular flask, and the mixture was shaken at 120 r / min for 6 h at room temperature (~23 ° C). Then, the mixed suspension was filtered (0.22 μm filter membrane), the filtrate was collected, and the residual heavy metal content was determined by inductively coupled plasma mass spectrometry (ICP-MS). The adsorption amount of heavy metals was calculated to evaluate the adsorption passivation effect of sodium hydroxide modified biochar composite material and unmodified biochar on heavy metals.
[0040] The results showed that the adsorption capacity of heavy metals by unmodified biochar was low, among which Cd 2+ The adsorption capacity is between 1.02~2.15mg / g, Pb 2+ The adsorption capacity is between 3.21~5.11mg / g, Cr 6+ The adsorption capacity is between 2.04 and 2.45 mg / g. 5+The adsorption capacity is between 0.56 and 0.83 mg / g. The sodium hydroxide modified biochar composite materials prepared in Examples 1 to 4 have a higher adsorption capacity for heavy metal ions, among which Cd 2+ The adsorption capacity is between 5.66~7.74mg / g, Pb 2+ The adsorption capacity is between 9.19 and 9.95 mg / g, Cr 6+ The adsorption capacity is between 6.40 and 7.27 mg / g. 5+ The adsorption amount was between 5.77 and 7.13 mg / g. This result shows that compared with unmodified biochar, the sodium hydroxide modified biochar composite material has a good heavy metal adsorption passivation effect.
[0041] Taking the sodium hydroxide modified biochar composite material prepared in Example 1 as an example, an experiment on the adsorption effect of heavy metals in compost was conducted, specifically: when removing heavy metal pollutants in compost, the initial materials of the compost were chicken manure and bagasse, respectively, which were mixed at a mass ratio of 5:1 and evenly divided into three portions, each of which was about 70L, for standby use. Then, the unmodified biochar or sodium hydroxide modified biochar composite material prepared in Example 1 was fully mixed with the chicken manure bagasse compost mixture at 10% of the dry basis mass of the material, and the initial C / N ratio and moisture content of the compost were adjusted to about 25 and 60%, and after mixing evenly, it was loaded into a 60L compost fermentation tank, and a temperature probe was inserted in the upper part to monitor the temperature change of the pile (set to measure once every 10 minutes), and intermittent ventilation was used, the ventilation rate was set to 0.4L•kg / h, ventilation was 30 minutes per hour, and paused for 30 minutes to ensure smooth composting. For convenience, the chicken manure-bagasse compost mixture without any biochar was recorded as CK, the chicken manure-bagasse compost mixture with unmodified biochar was recorded as BC, and the chicken manure-bagasse compost mixture with sodium hydroxide modified biochar composite material was recorded as SHBC. The aerobic fermentation composting test period was 35 days. Random sampling was carried out in the upper, middle and lower layers on the 0th day and the 35th day. The BCR sequential extraction method promoted by the European Union was used to obtain the different forms of heavy metals (Cd, Pb, Cr, As). At the same time, the total amount of heavy metals (Cd, Pb, Cr, As) was determined to calculate the proportion of different forms in the total amount and the passivation rate. The passivation rate test results are shown in Figure 6 Heavy metals (Cd, Pb, Cr, As) were determined using inductively coupled plasma mass spectrometry (ICP-MS) (GB / T25282-2010).
[0042] The total amount of heavy metals (Cd, Pb, Cr, As) and their forms during composting Figure 5The results show that after composting, the exchangeable state of Cd in unmodified biochar and sodium hydroxide modified biochar was 10.13% and 5.74%, and the reduced state was 49.34% and 37.15%, respectively; the exchangeable state of Pb was 15.52% and 11.05%, and the reduced state was 11.09% and 6.86%, respectively; the exchangeable state of Cr was 5.95% and 4.29%, and the reduced state was 11.03% and 5.03%, respectively; the exchangeable state of As was 23.49% and 20.72%, and the reduced state was 10.52% and 8.48%, respectively. Passivation rate: The passivation rates of unmodified biochar for heavy metals are Cd: 33.21%, Pb: 17.21%, Cr: 28.13%, As: 23.35%, and the passivation rates of sodium hydroxide modified biochar for heavy metals are Cd: 57.30%, Pb: 43.69%, Cr: 33.78%, and As: 44.35%. This result shows that compared with unmodified biochar, sodium hydroxide modified biochar composite material has a good adsorption and passivation effect on compost heavy metals.
[0043] In order to verify the heavy metal removal capacity of the modified biochar material multi-material, the aerobic composting parameters in the adsorption effect experiment of heavy metals in compost were used. The initial composting materials were sludge and straw, respectively, and the two were fully mixed at a dry basis weight of 2:1 for standby use. Then, the unmodified biochar or sodium hydroxide modified biochar prepared in Example 1 was co-composted with sludge and straw at 3% of the dry basis weight of the material, and the initial C / N ratio and moisture content were adjusted to about 25 and 60%, respectively. After mixing evenly, the composting fermentation tank was loaded. The sludge and straw compost mixture without any biochar was recorded as T1, the sludge and straw compost mixture with unmodified biochar was recorded as T2, and the sludge and straw compost mixture with sodium hydroxide modified biochar was recorded as T3. The determination of heavy metals (Cd, Pb, Cr, As) was carried out by inductively coupled plasma mass spectrometry (ICP-MS) (GB / T25282-2010).
[0044] The passivation rate of the total amount of heavy metals (Cd, Pb, Cr, As) during the composting process is as follows: Figure 7 As shown. The results show that the passivation rate of unmodified biochar for heavy metals is Cd: 29.84%, Pb: 15.45%, Cr: 25.32%, As: 21.07%, and the passivation rate of sodium hydroxide modified biochar composite material for heavy metals is Cd: 65.91%, Pb: 50.31%, Cr: 38.86%, and As: 46.47%. This result shows that compared with unmodified biochar, sodium hydroxide modified biochar has a good adsorption and passivation effect on heavy metals in sludge and straw compost.
[0045] In order to verify the heavy metal removal capacity of modified biochar materials, the aerobic composting parameters in the adsorption effect experiment of heavy metals in compost were used. The initial composting materials were pig manure, chicken manure, cow manure and corn stalks, respectively. After the four were fully mixed at a dry basis weight of 1:1:1:1, they were evenly divided into 3 parts for standby. Then, the unmodified biochar or sodium hydroxide modified biochar composite material prepared in Example 1 was co-composted with pig manure, chicken manure, cow manure and corn stalks at 8% of the dry basis weight of the material. For convenience, the sludge and straw compost mixture without any biochar was recorded as CL, the sludge and straw compost mixture with unmodified biochar was recorded as BC, and the sludge and straw compost mixture with modified biochar was recorded as BC@sodium hydroxide. The composting test period was 49 days. The determination of heavy metals (Cd, Pb, Cr, As) was carried out by inductively coupled plasma mass spectrometry (ICP-MS) (GB / T25282-2010).
[0046] The passivation rate of the total amount of heavy metals (Cd, Pb, Cr, As) during the composting process is as follows: Figure 8 As shown. Passivation rate: The passivation rates of unmodified biochar for heavy metals are Cd: 32.04%, Pb: 15.50%, Cr: 32.27%, As: 25.95%, respectively. The passivation rates of sodium hydroxide modified biochar composite materials for heavy metals are Cd: 61.72%, Pb: 39.20%, Cr: 38.80%, and As: 44.90%. This result shows that compared with unmodified biochar, sodium hydroxide modified biochar composite materials have good adsorption and passivation effects on heavy metals in multi-element livestock and poultry manure and corn straw aerobic composting.
[0047] The above contents are only for explaining the technical idea of the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.
Claims
1. A method for preparing a sodium hydroxide modified biochar composite material, characterized in that: The following steps are involved: The agricultural waste material is shredded, cleaned, dried, and then sealed. After standing, an inert atmosphere is introduced for pyrolysis reaction. After cooling, grinding, and sieving, a crude biochar is obtained. The crude biochar is mixed with a sodium hydroxide solution, and the liquid is filtered out after shaking to leave the solid. The solid is washed until the filtrate is neutral, and then dried to obtain a sodium hydroxide-modified biochar composite material. The solid-liquid ratio of the crude biochar to the sodium hydroxide solution is 1 g: (5-10) mL. The concentration of the sodium hydroxide solution is 1.0-4.0 mol / L.
2. The method for preparing a sodium hydroxide modified biochar composite material according to claim 1, characterized in that: The agricultural waste materials include one or more of dry straw, wood chips, dry grass, dry leaves and dry branches.
3. The method for preparing a sodium hydroxide modified biochar composite material according to claim 1, characterized in that: The drying temperature is 60-80°C.
4. The method for preparing a sodium hydroxide modified biochar composite material according to claim 1, characterized in that: The conditions of the pyrolysis reaction are: pyrolysis at 600-650° C. for 2-6 hours.
5. The method for preparing a sodium hydroxide modified biochar composite material according to claim 1, characterized in that: The heating rate of the pyrolysis reaction is 5-10°C / min.
6. The method for preparing a sodium hydroxide modified biochar composite material according to claim 1, characterized in that: The particle size of the crude biochar is less than 100 mesh.
7. The method for preparing a sodium hydroxide modified biochar composite material according to claim 1, characterized in that: The shaking conditions are: shaking at 15-40° C. and a speed of 120-180 r / min for 6-8 hours.
8. The method for preparing a sodium hydroxide modified biochar composite material according to claim 1, characterized in that: The cleaning is performed using deionized water.
9. A sodium hydroxide modified biochar composite material, characterized in that: Prepared according to the preparation method according to any one of claims 1 to 8.
10. Use of a sodium hydroxide modified biochar composite material according to claim 9 in adsorption and passivation of heavy metals in compost.